2014
DOI: 10.1016/j.nutres.2014.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fatty acids alter left ventricular myocardial gene expression in Wistar rats

Abstract: Obesity increases the risk for cardiomyopathy in the absence of comorbidities. Myocardial structure is modified by dietary fatty acids. Left ventricular (LV) hypertrophy is associated with Western diet consumption, while intake of n-3 polyunsaturated fatty acids (PUFA) is associated with antihypertrophic effects. We previously observed no attenuation of LV thickening following 3 months of docosahexaenoic acid (DHA) supplementation of a Western diet, compared to Western diet intake alone, in rats that had simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 67 publications
1
2
0
Order By: Relevance
“…The current result lends credence to the report of Jeckel et al [26] who demonstrated that in rats, BTG2 gene was downregulated when dietary fatty acid was fed. Therefore, lack of BTG2 upregulation in the in the blood of cows in the present study would be due to the fatty acid content of the fed diet.…”
Section: Btg2supporting
confidence: 90%
“…The current result lends credence to the report of Jeckel et al [26] who demonstrated that in rats, BTG2 gene was downregulated when dietary fatty acid was fed. Therefore, lack of BTG2 upregulation in the in the blood of cows in the present study would be due to the fatty acid content of the fed diet.…”
Section: Btg2supporting
confidence: 90%
“…Anesthesia was induced and maintained using isofluorane [19]. A surgical plane of anesthesia was confirmed when a toe pinch failed to elicit a change in respiratory rate or pattern.…”
Section: General Anesthesiamentioning
confidence: 99%
“…Total RNA concentration was determined using a NanoDrop ND-1000 Spectrophotometer (NanoDrop Technologies, Wilmington, DE, USA) [19]. Complementary DNAs were prepared using the M-MLV Reverse Transcriptase (Invitrogen) with a Random Primer (TaKaRa, Otsu, Japan).…”
Section: Total Rna Isolation and Complementary Dna Synthesismentioning
confidence: 99%